Comprehensive studies of biological characteristics, phytochemical profiling, and antioxidant activities of two local citrus varieties in China - Sun, Lifang; Xu, Jianguo; Nasrullah,; Wang, Luoyun; Nie, Zhenpeng; Huang, Xiu; Sun, Jianhua; Ke, Fuzhi (Frontiers in Nutrition, 2023)
Citrus is widely grown all over the world, and citrus fruits have long been recognized for their nutritional and medical value for human health. However, some local citrus varieties with potentially important value are still elusive. In the current study, we elucidated the biological characteristics, phylogenetic and phytochemical profiling, antioxidants and antioxidant activities of the two local citrus varieties, namely Zangju and Tuju. The physiological and phylogenetic analysis showed that Zangju fruit has the characteristics of wrinkled skin, higher acidity, and phylogenetically closest to sour mandarin Citrus sunki, whereas, Tuju is a kind of red orange with vermilion peel, small fruit and high sugar content, and closely clustered with Citrus erythrosa. The phytochemical analysis showed that many nutrition and antioxidant related differentially accumulated metabolites (DAMs) were detected in the peel and pulp of Zangju and Tuju fruits. Furthermore, it was found that the relative abundance of some key flavonoids and phenolic acids, such as tangeritin, sinensetin, diosmetin, nobiletin, and sinapic acid in the peel and pulp of Zangju and Tuju were higher than that in sour range Daidai and satsuma mandarin. Additionally, Zangju pulp and Tuju peel showed the strongest FRAP activity, whereas, Tuju peel and pulp showed the strongest DPPH and ABTS free radical scavenging activities, respectively. Moreover, both the antioxidant activities of peel and pulp were significantly correlated with the contents of total phenols, total flavonoids or ascorbic acid. These results indicate that the two local citrus varieties have certain nutritional and medicinal value and potential beneficial effects on human health. Our findings will also provide an important theoretical basis for further conservation, development and medicinal utilization of Zangju and Tuju.